Under-reported: child pedestrian road traffic injuries in Vietnam. (7th October 2012) - Brondom, L; Florian, M
Abstract : Background: Despite increased motorisation in Vietnam, walking remains an important mode of transport, particularly amongst children. Official 2011 statistics report 11 950 road traffic fatalities. However, they do not specify pedestrian injuries. Objectives: The study aimed to assess the magnitude of child pedestrian road traffic injuries (RTI) in Dong Nai province, Vietnam. Methods: Police and hospital data on RTI from 2010 to first quarter 2012 was analysed. Moreover, a survey collected information from approximately 6800 primary students in 2010 and 2011. Results: Data sources show that RTI in Dong Nai have increased compared to 2010. Dong Nai General Hospital reports seven pedestrian RTI cases, all of which were under the age 16. Comparatively, one forth of RTI at the paediatric hospital were pedestrians. In 2011, 3% of students reported having been injured by a vehicle walking to and from school within 6 months; accounting for an estimated 5900 to 7800 primary students in Dong Nai. Significance: Results indicate that official data sources do not capture the magnitude of pedestrian casualties in Dong Nai, Vietnam. Reliable estimates of these indicators are essential to guide policy and intervention, and for evaluation purposes. Data indicates that children under 16 are at greatest risk for pedestrian injury, suggesting schools as the key target for intervention. As implementer of SafeKids Vietnam, Asia Injury Prevention Foundation dedicates its efforts to addressing this issue.